(untitled) (Applied Biological Research, 2017)
The study was aimed to assess the compatibility of intra-specific mandarin crosses and germination of F1 seeds under sub-tropical conditions of Punjab (India). Experiment was conducted at PAU, Ludhiana (Punjab) during 2014 and 2015. Six hundred crosses were made in each of four type crosses viz., ‘Daisy x Kinnow’, ‘Kinnow x Daisy’, ‘W. Murcott x Kinnow’ and ‘Kinnow x Murcott’. After harvest of mature fruits from each cross, the F1 seeds were sown under protected conditions. Results showed that the mean fruit set percentage was maximum (15.49) in ‘W. Murcott x Kinnow’ cross but was at par with ‘Kinnow x W. Murcott’ cross (14.16) and significantly higher than other crosses. Mean minimum fruit drop (31.87%) was observed in ‘Kinnow x W. Murcott’ which was at par with ‘Kinnow x Daisy’ and ‘W. Murcott x Kinnow’ crosses (32.29 and 34.79% fruit drop, respectively). The mean normal seed number fruit-1 was maximum (21.21) in fruits from ‘Kinnow x Daisy’ cross but was at par with ‘Kinnow x W. Murcott’ cross (18.01). Maximum number of seedlings seed-1(1.17) emerged from ‘W. Murcott’ as female parent when ‘Kinnow’ was used as male parent which was at par with other crosses, except ‘Daisy x Kinnow’ which recorded single seeding seed-1. The results revealed clear-cut difference in physiological mechanism controlling these parameters among these intra-specific crosses in mandarin.